A molecular perspective on the family Testudinidae batsch, 1788 - Cunningham, Jessica (Division of Chemical Pathology, 2002)
Bibliography: leaves 228-252. The Family Testudinidae have a diverse distribution and, although limited to tropical and subtropical latitudes, are present on all continents with the exception of Australia and Antartica. Their evolutionary history dates back to the late Paleogene at least, and periods of diversification and expansion appear to be closely associated with global climate change, particularly at the border of the Oligocen-Miocene transition.